Head and Neck Cancer Imaging - Hermans, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Imaging is crucial in the multidisciplinary approach to head and neck cancer management. The rapid technological development of recent years makes it necessary for all members of the multidisciplinary team to understand the potential applications, limitations, and advantages of existing and evolving imaging technologies. It is equally important that the radiologist has sufficient clinical background knowledge to understand the clinical significance of imaging findings. This book provides an overview of the findings obtained using different imaging techniques during the evaluation of head and neck neoplasms, both before and after therapy. All anatomic areas in the head and neck are covered, and the impact of imaging on patient management is discussed in detail. The authors are recognized experts in the field, and numerous high-quality images are included. This second edition provides information on the latest imaging developments in this area, including the application of PET-CT and diffusion-weighted magnetic resonance imaging.
Introduction: Epidemiology, Pathology, Risk Factors, and Natural History of Head and Neck Neoplasms -- Clinical and Endoscopic Examination of the Head and Neck -- Imaging Techniques -- Laryngeal Neoplasms -- Neoplasms of the Hypopharynx and Proximal Esophagus -- Neoplasms of the Oral Cavity -- Neoplasms of the Oropharynx -- Neoplasms of the Nasopharynx -- Parapharyngeal Space Neoplasms -- Masticator Space Neoplasms -- Neoplasms of the Sinonasal Cavities -- Salivary Gland Neoplasms -- Skull Base Neoplasms.-Thyroid and Parathyroid Neoplasms -- Neck Nodal Disease -- Neck Lymphoma -- PET in Head and Neck Cancer -- Use of Imaging Data in Radiotherapy Planning of Head and Neck Cancer.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Radiotherapy; Oncology; Head -- Surgery; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Head and Neck Surgery; Oncology; Radiotherapy; Nuclear Medicine